Institutional Revitalization of Ludruk Wetanan in Jember Upon Facing The Competition in Entertainment Industry - Akhmad Taufiq; Furoidatul Husniah; Siswanto Siswanto (Pancaran Pendidikan, 2018)
This paper describes the phenomenon of ludruk wetanan in Jember which experienced institutional problems. Institutional problems include; the administrative system is still weak, the actor's regeneration system and actresses are weak, and the ludruk gamelan (musical instrument) is old. Therefore, this community partnership program is directed at addressing partner problems, which are focused on the three institutional issues. With the achievement of the three partner problems, it is expected that the ludruk group can face the competition in the entertainment market industry; including maintaining existence and permanence. For this reason, a method was developed to overcome the problems of the partners, namely by developing the capacity of an institutional system based on three pillars (system development based on three pillars); namely, a system of cooperation between the implementing parties (teams), target partner groups, and market participants to contribute to the institutional revitalization process. Therefore, the results of this service program cover three things. First, related to the revitalization of the administration system, the ludruk group is willing to work with the team to design and make the draft AD/ART as the basic foundation of the administrative system of the arts organization. Secondly, from the revitalization side of the generation, the Setia Kawan Jember ludruk group has carried out a regeneration system by carrying out structural arrangements, replacing Manager of ludruk followed by a fairly good pattern of division of tasks between skipper and vice-boss. Third, in terms of property revitalization, this Setia Kawan Jember group has done two things; namely making stage performances and repair/maintenance for the ludruk gamelan.